Curious Case of Swelling over the Back: A Case Report of Sebaceous Cell Carcinoma in a Patient of Airborne Contact Dermatitis - Sonia Jain; Sangeeta Galui; Pratiksha Sonkusale (Wolters Kluwer Medknow Publications, 2024)
Sebaceous carcinoma is a rare variety of malignant tumor involving sebaceous glands. Compared to its ocular counterpart, the extraocular variant is even more rare, accounting for only one-fourth of all cases. It is a great mimicker of a plethora of benign and malignant tumors, hence often misdiagnosed. Surgical excision is the preferred mode of treatment in most cases. Here, we present the case of a 72-year-old male with airborne-contact dermatitis who was initially misdiagnosed with acrochordon, which was later found to be a case of sebaceous carcinoma on histopathology. There is a paucity of literature regarding sebaceous gland carcinomas located outside the head-and-neck region, which makes this case even more interesting.